Investigating ferric ion production and consumption trends in a simulated e-waste bioleaching environment for maximum metal dissolution efficiency - Gituma, Mark Kinoti (Centre for Bioprocess Engineering Research, 2017)
Electrical and electronic equipment has become an integral part of life in the modern world. When disposed of, it is termed Waste Electrical and Electronic Equipment (WEEE) and is one of the fastest growing waste streams in the world. Disposing the WEEE has associated risks as they contain a high amount of toxic metals (e.g. lead) which can leach into the soil, they place a high load on the land and they contain valuable metals making their recovery beneficial. Printed circuit boards (PCBs) are an essential part of WEEE. Although WEEE forms a small part of the waste stream (3 %), it contains a high concentration of metals. As such, PCBs form the focus of this study. Base metals, especially copper, hamper the recovery of gold and PGMs by cyanidation. Further the copper grades of WEEE exceed those of many low grade ores exploited. Hence copper recovery from PCBs has garnered considerable focus. Bioleaching using the ferric ion and ferrous ion regeneration cycle is applied to the recovery of metals from metal sulphides in virgin ores and there is growing interest in its application to WEEE. The two sub-processes in the ferric regeneration cycle are ferric ion production through microbial oxidation of ferrous ion for growth and metabolic activity; and ferric ion consumption through the reduction of metals leading to metal dissolution. The ferric ion consumption and production rates depend on each other and other factors. The metal dissolution through ferric iron reduction is a function of ferric iron concentration, affected by how fast ferric iron is produced through microbial oxidation. Ferric iron production is a function of both the ferrous iron and ferric iron concentrations and so depends on how fast the ferrous ion substrate is produced through the dissolution of metals which consumes ferric ion in the process. Ferric ion production is also affected by the microbial population and microbial specific rates of oxidation of ferrous ion. Ferric ion consumption is also dependent on the metal dissolution rate which is affected by mass transfer limitations and the type of metal for dissolution. These are two competing subprocesses where the dissolution efficiency of metals is limited by the slower process.